SEIR model related to COVID 19 spread and forecasting number of death / Maznah Banu Mohamed Habiboo Raman ... [et al.] - Mohamed Habiboo Raman, Maznah Banu; Mohamad Salehhudin, Amirah Alia Syakilla; Md Hussin, Nur Syahirah; Nizam, Nur Azmina (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The World Health Organization (WHO) China Country Office reported on December 31, 2019, of occurrences of pneumonia with an unknown etiology. Community infection, group infection, and widespread transmission are the three phases of COVID-19’s outbreak. It has aggressively spread around the world, especially to Malaysia. Currently, Malaysia has reported 8,574 cases and 102 deaths as of July 12, 2021. Symptoms might show anywhere between two and fourteen days after being infected with the virus. In this study, we will be using the Susceptible-Exposed-Infectious-Recovered (SEIR) model as an estimation tool to develop the number of COVID-19 cases in Malaysia. The model is being used to anticipate things like how quickly a disease will spread, how many people will become affected, and what steps can be taken to slow it down. To forecast the number of COVID-19 deaths in Malaysia, we used two different methods which are Least Square Method and Holt-Winters Method to choose the best method that is more accurate. In order to determine the possible case in the future, the researchers use the SEIR model to study COVID-19 cases in Malaysia and the Least Square Method and Holt-Winters Time Series to identify the number of COVID-19 deaths in Malaysia by using data on October 2021.